The interrelationships between economic growth and innovation: international evidence - Duyen My Thi Thi; Tinh Tran Phu Do (Journal of Applied Economics, 2024)
Technological innovation towards the goal of sustainable development is one of the concerns of many countries. This research investigates the linkages between innovation and growth for 71 countries worldwide from 1996 to 2020 by employing a simultaneous equation model and the three-stage least squares method to examine the bidirectional linkages among the variables. Outcomes state a two-way relation between growth and technology innovation. Specifically, a positive influence of technology innovation on economic expansion emphasizes the importance of innovation in growth. Meanwhile, a negative relationship between growth and technology innovation shows that the pressure of growth hinders innovation. Furthermore, a bidirectional relationship still exists between them in the sample of high-upper-middle-income countries but only one way for low-lower-middle-income countries. Institutional quality positively affects growth, while institutional quality has a negative influence on innovation. A number of policies have proposed to help promote innovation and enhance economic growth.